The implementation of the United Nations security council resolutions on Libya - Safwat, Mostafa Ahmed Mostafa (AUC Knowledge Fountain, 2017)
The situation in Libya in February 2011 turned into a violent civil war between what was viewed at the time as peaceful protestors calling for the Qaddafi regime to step down and the Qaddafi regime forces. This resulted in international condemnation and action by many countries and international organizations such as the League of Arab States, the United Nations and the North Atlantic Treaty Organization. The United Nations Security Council adopted resolutions 1970 and 1973 in 2011 to protect the civilian population in Libya from Qaddafi's forces. These resolutions paved the way for an international military intervention in Libya. This project looks into the extent to which the UN mandate was exceeded during the implementation of the resolutions - if at all. The resolutions mandate was the protection of civilians and not regime change, yet the military intervention that took place over Libya through Operation Odyssey Dawn and which later shifted to the NATO-led Operation Unified Protector resulted in regime change in Libya. Countries who participated in the military intervention in Libya, such as USA, UK and France, among many others and later on NATO, as well as non-NATO countries 'exceeded the UNSC resolutions' mandate because of their resort to direct military intervention, and went to war against Qaddafi's forces as opposed to adhering to an imposition of a NFZ to protect civilians as the resolution stated.The mandate had been stretched beyond neutralizing Gadhafi's aerial capacities. Countries that directly and openly armed the Libyan rebels to fight against the Qaddafi regime also went beyond the letter of the UNSC resolutions.